An overview on methods for the production of carbon nanotubes - Mujawar, Mubarak; Abdullah, E.; Jayakumar, N.; Sahu, J. (Elsevier, 2014)
Carbon nanotubes (CNTs) are one of the most exciting discoveries in nanoscale sciences. A brief survey of experimental work directed towards the synthesis of CNTs has been discussed. The various methods of production of CNTs are explained outlining their capabilities, efficiencies and possible exploitation as economic large scale production. Among the discussed techniques, the chemical vapor deposition (CVD) appears to be the most potential way to produce high quality of CNTs at high yield. The advantages of CVD over other techniques are also explained and the effects of process parameter on the synthesis of these nanomaterials are discussed.